Basic properties of crude rubber seed oil and crude palm oil blend as a potential feedstock for biodiesel production with enhanced cold flow characteristics - Yusup, Suzana (Elsevier, 2010)
Research and development in the field of biodiesel showed that fatty acid methyl esters synthesized from agriculture or animal oils and fats, which exhibit qualifying properties, can replace diesel fuel used in internal combustion engine. However, the industry had some downfall recently with the fluctuating prices of edible oils and increasing demand for nutritional needs. Crude rubber seed oil (CRSO) and crude palm oil (CPO) were used in this study since both can be extracted and produced locally in Malaysia from their abundant plantations. The benefits of introducing such blend are that CRSO is considered a nonedible feedstock with no major industrial utilizations that has the potential to reduce the usage of CPO in biodiesel industry and was found to enhance the cold flow characteristics when blended with CPO by reducing the saturated fatty acids in the feedstock. The oils and blends were characterized for density, kinematic viscosity, heating value, acid value, free fatty acid content, refractive index, mono-, di- and triglycerides and sulphur content. Fatty acids composition and iodine value were established for an equivolume blend of the oils.